The impact of owner-managers' personality traits on their small hospitality enterprise performance in Saudi Arabia - Abu Elnasr E. Sobaih; Amer A. Al-qutaish; Hassane Gharbi; Ahmed E. Abu Elnasr (Journal of Risk and Financial Management, 2022)
Governments in many countries have paid close attention to small enterprises because of their social and economic impacts. The role of the owner-manager in advancing the performance of their small business cannot be underestimated. The current study tests the influence of an owner-manager's big five personality traits on the performance of their small enterprises. For this purpose, a pre-tested questionnaire was directed to owner-managers of small hospitality enterprises in Saudi Arabia. The results of SEM analysis, with AMOS, showed that high levels of both openness to experience and agreeableness of owner-managers have a significant positive impact on the performance of their small enterprises. However, a high level of neuroticism has a significant negative impact on the performance of their small enterprises. The results interestingly showed that high levels of both conscientiousness and extraversion among owner-managers have positive, but insignificant, impacts on the performance of their small enterprises. These two traits had a minor impact on the performance of small hospitality enterprises. Hence, managers of small hospitality enterprises in Saudi Arabia are required to have high levels of openness to experiences and agreeableness and low level of neuroticism to achieve significant organizational performance.
Keywords: 650; enterprise performance; owner-managers; personality traits; Saudi Arabia (SA); small hospitality enterprises